Pengaruh Silica Gel dan Waktu Pengeringan Terhadap Penurunan Kadar Air dan Viabilitas Benih Kedelai Anjasmoro - Pramaditya Taufik Zulfikar; Muharam Muharam; Darso Sugiono; Nurul Hidayatun (Jurnal Ilmiah Wahana Pendidikan, 2021)
Soy plant (Glycine max L.) has an important meaning to meet food needs in order to improve the nutrition of the society. Based on previous research, the provision of seeds in sufficient and timely quantities is often constrained due to improper seed processing and the initial moisture content of seeds before relatively high storage. This then attracted the attention of the authors to research to find out whether there is an interaction between silica gel treatment with drying duration to decreased moisture content and seed viability and the growth and yield of soybean varieties of Anjasmoro using experimental methods with Complete Random Design (RAL) 2 factors and the treatment is repeated 3 times so that 12 samples are obtained. The results achieved from this study are that there is an interaction between silica gel treatment and the duration of drying of seed moisture content, seed viability, and the growth and yield of soybean plants (Glycine max L.). The tallest plant of 68 cm is achieved by control treatment with a drying length of 2 weeks. The highest yield weight per plant of 147 grams was achieved by the Control s0 treatment with a drying duration of 2 week.